PENGARUH SOLVABILITAS, LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN KELOMPOK INDUSTRI AUTOMOTIVE DAN KOMPONENNYA DI BEI - Lilis Saidah Napisah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
Abstract : Stock as one of the investment instruments in the capital markets , an attractive option for investors . The expected return on this investment is the dividend or capital gain . Fundamental factors issuer is a factor that is closely related to the condition of the company , namely the condition of human resource management organization , financial condition reflected in the performance of the work . Analysis of solvency , liquidity and profitability investigated whether partially or simultaneously there is significant influence on stock price movements . Data processing techniques using Multiple Linear Regression and Correlation , with the SPSS program ( Anova ) , including the significance test F with a confidence level of 95 % . Finding found seen from R square of 32.50 percent , comes from the variable solvency , liquidity and profitability , the rest comes from other variables . Of the test F , three variables simultaneously have significant influence on stock prices because it has the Sig < 0.05 .